The Interplay of Emotional Intelligence Abilities and Work Engagement on Job and Life Satisfaction: Which Emotional Abilities Matter Most for Secondary-School Teachers? - Mérida-López, Sergio; Extremera, Natalio (Frontiers in Psychology, 2020)
Emotional intelligence has been underscored as a helpful personal resource in explaining life and job attitudes in human services employees. However, the joint interaction of emotional intelligence abilities with work engagement to explain life and job attitudes has not been tested. The present study aimed to explore the interactive role of emotional intelligence abilities with work engagement in the prediction of job and life satisfaction in a sample of Spanish secondary-school teachers. A total of 190 teachers (125 females) participated in the study. Notably, the results showed that only emotion regulation ability was significantly associated with work engagement, job satisfaction, and life satisfaction. Furthermore, emotion regulation ability moderated the relationship between work engagement and job and life satisfaction. The present findings contribute to current knowledge on emotional intelligence abilities and personal and job-related correlates of teachers’ work engagement.